Murine Cytomegalovirus Infection Induces Susceptibility to EAE in Resistant BALB/c Mice - Milovanovic, Jelena; Popovic, Branka; Milovanovic, Marija; Kvestak, Daria; Arsenijevic, Aleksandar; Stojanovic, Bojana; Tanaskovic, Irena; Krmpotic, Astrid; Arsenijevic, Nebojsa; Jonjic, Stipan; Lukic, Miodrag L. (Frontiers in Immunology, 2017)
In contrast to C57BL/6 mice, BALB/c mice are relatively resistant to the induction of experimental autoimmune encephalomyelitis (EAE) after challenge with MOG35-55 peptide. Here we provide the first evidence that infection with murine cytomegalovirus (MCMV) in adulthood abrogates this resistance. Infected BALB/c mice developed clinical and histological signs similar to those seen in susceptible C57BL/6 mice. In addition to CD4+ cells, large proportion of cells in the infiltrate of diseased BALB/c mice were CD8+, similar with findings in multiple sclerosis (MS). CD8+ cells that responded to ex vivo restimulation with MOG35-55 were not specific for viral epitopes pp89 and m164. MCMV infection favors proinflammatory type of dendritic cells (CD86+CD40+CD11c+) in the peripheral lymph organs, M1 type of microglia in CNS, and increases development of Th1/Th17 encephalitogenic cells. This study indicates that MCMV may enhance autoimmune neuropathology and abrogate inherent resistance to EAE in mouse strain by enhancing proinflammatory phenotype of antigen presenting cells, Th1/Th17 and CD8 response to MOG35-55.